“Going on a sensory adventure, a touchy subject?”: investigating haptic technology and consumer adventure orientation - Mulcahy, Rory Francis; Riedel, Aimee (Journal of service theory and practice, 2022)
PurposeThe purpose of this paper is twofold. First, it seeks to extend service and retailers understanding of how the inclusion of haptics can gamify digital service experiences. Second, it seeks to understand the moderating role of consumers orientation towards adventure in service experiences.Design/methodology/approachThis research adopts a two-study, 2 (haptic technology: present vs absent) × 2 (adventure orientation: high vs low) to test the proposed hypotheses (Study 1 n = 210, Study 2 n = 452). The data are tested using ANCOVA's and Hayes PROCESS Macro to investigate mean differences and the potential presence of two different moderated mediated relationships.FindingsThe results are consistent across the two experimental studies evidencing that the inclusion of haptics to gamify the service experience leads to significantly improved outcomes for service brands and channels. Further, the results demonstrate that the impact of haptics is greater for consumers with a lower, compared to higher, sense of adventure. Thus, the results demonstrate that whilst haptics improves consumers experiences with technological services overall, this is more prevalent for those who have “less sense of adventure”.Originality/valueThis paper sheds insight into the emerging area of haptic technology and is one of the first to specifically examine the impact of consumers “sense of adventure.”